ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH PADA LOYALITAS PELANGGAN DI ALFAMART JAKARTA BARAT - Siti Nurjanah (Yayasan Akrab Pekanbaru, 2019)
The aim of this research is to analyze the impact of service quality, promotion and product quality on costumer loyalty at Alfamart. The population of this research is the Alfamart customers in West Jakarta which is unlimited.The survey method has been done for 50 respondents that accidentally shopped to Alfamart. The collected data have been analyzed by correlation test, t- test and F test.The results from the correlation test analyses could be concluded that there were correlations among the independent variables toward the dependent variable. The result from t-test could be concluded that among the independent variables to dependent variables had less significance influence. The result from F test could be concluded that service quality, promotion and product quality had significant influence to costumer loyalty.